ENT600: Tok Janggut burger stall / Faridatul Akma Abd Ghani, Mohammad Naqib Ihsan Mohd Nazri and Mohd Adhwa Mohd Ayob. - Abd Ghani, Faridatul Akma; Mohd Nazri, Mohammad Naqib Ihsan; Mohd Ayob, Mohd Adhwa (2018)
Burger is a very popular food among Malaysians. It is one of the cheapest foods around. This case study is about Tok Janggut Burger stall located at Jalan Ronggeng 3 Taman Skudai Baru, Johor Bahru. But the waiting time for the customer is longer during the burger process. It's can affect the loyalty of the customer.